The Effect of Profitability and Managerial Ownership on Financial Distress with Capital Structure as Moderating Variable - Ardi, Sulasman; Windijarto (GoAcademica Research & Publishing, 2023)
This study is being conducted as a continuation of previous research and intends to ascertain the impact of management ownership and profitability on financial distress moderation of capital structure. ROE predicts profitability, while DER predicts the capital structure. Financial reports and yearly reports are used in the research to round out the facts. The Indonesia Stock Exchange's (IDX) tourist industry was the population and sample, and the observation period was from 2019 to 2021. SPSS software is used for data analysis to evaluate the hypothesis. The findings demonstrate that managerial ownership and profitability have an impact on financial distress in tourism sector enterprises, and that the capital structure modifies the relationship between managerial ownership and profitability in this regard.